Shaping the Common Labor Market between Denmark and Sweden: Lessons for Sustainable Development - Plaskonis, Kate (European Journal of Sustainable Development, 2019)
Though Denmark and Sweden have had a similar historical development over the years, the differences in their labor markets have become more visible than ever. While the labor shortage is increasing in Copenhagen, there is a high number of unemployed individuals with a more substantial proportion of vulnerable groups among them in Sweden. Despite some appealing factors (such as less governed labor law, the simplicity of employing and the high wages), the interest of Swedes to work in Copenhagen area has decreased, and as a result, the number of commuters has fallen. Could it then be employers’ attitudes towards foreign-born individuals that differ? Through interviewing Swedish and Danish employers and foreign-born population, Fördomsfönster Öresund project investigates if the attitudes differ and how social sustainability and utilizing the existent competence frame a common regional labor market. Interviews show that some concepts might be crucial in addressing the issue: language, prejudice, leadership and the difference in perceptions. By informing and responding to these problem areas, there is a strong possibility of greater integration, competence-based employment and higher revenues in commuting within the region. Keywords: Diversity, competence, social sustainability, labor market, green commuting